Analysis of GEMOHING Organizational Culture in Supporting Business Practices - Lusia Tuto Boli Ina; Rolland E Fanggidae; Muhamad Dian Aryono; Tarsisius Timuneno (Jurnal Studi Multidisiplin Ilmu, 2024)
Purpose: This study aims to analyze the implementation of GEMOHING organizational cultural values in supporting cooperative business practices and identify the supporting and inhibiting factors. Methodology/approach: This study employed a qualitative approach with a descriptive design. The research informants consisted of 10 people, including the cooperative manager and employees, who were selected using purposive sampling method. Data were collected through interviews, observations, and documentation, and data analysis was performed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. Results: GEMOHING cultural values such as mutual cooperation, efficiency, dignity, objectivity, conscience, integrity, neutrality, and generation have been implemented in daily work activities, particularly in teamwork, member services, and respectful working relationships. In addition, other cultural values such as kinship, open communication, and concern for members were identified, which further strengthened the implementation of organizational culture. However, the diversity of members’ backgrounds and limited time for work evaluation were found to be inhibiting factors in the optimal implementation of the organizational culture. Conclusions: GEMOHING’s organizational culture plays an important role in supporting cooperative business practices. Although it has been implemented, the level of understanding and internalization of these cultural values is still suboptimal. Limitations: This study was limited to a single cooperative and used a qualitative approach. Contributions: This study contributes to the development of organizational culture studies based on local wisdom, particularly in the context of cooperatives.